2018
DOI: 10.4103/1319-2442.235193
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological study of nephrotic syndrome in adults: A Moroccan report

Abstract: The reported causes of nephrotic syndrome (NS) varies between different countries. In this retrospective study, we aimed to evaluate the underlying causes of NS in adult patients who underwent renal biopsy in a region of Morocco and we also determined the distribution of histopathological diagnoses with regard to the age subgroups and genders from January 2007 to December 2016. Patients were divided into four groups according to age at the time of renal biopsy. A total of the 257 patients with NS were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Additionally, 8.3% of the patients had a different histological diagnosis than MCD, FSGS, or MGN. Another study by Yassir et al [11] revealed further insights into the underlying causes of NS within a larger context. Among the cases analyzed, membranous nephropathy (MN) emerged as the most prevalent cause, accounting for 22.2% of instances.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, 8.3% of the patients had a different histological diagnosis than MCD, FSGS, or MGN. Another study by Yassir et al [11] revealed further insights into the underlying causes of NS within a larger context. Among the cases analyzed, membranous nephropathy (MN) emerged as the most prevalent cause, accounting for 22.2% of instances.…”
Section: Discussionmentioning
confidence: 94%